Influence of the Talaqi and Tahsin Methods on the Al-Qur'an Reading Ability of Santri at the Al-Falah Islamic Boarding School Nagreg Bandung - Ibnu, Muhamad; Rahmawati, Shintia; Ridwansyah, Risyad Sani; Kariadinata, Rahayu; Susilawati, Wati (Journal of Modern Islamic Studies and Civilization, 2023)
The guide to the Islamic religion is the holy book Al-Qur'an, which should be read exactly according to the rules of Tajweed and understood as a guide to life. There are still students in this field who are not good at reading the Qur’an and need alternative methods to practice and improve their ability to read the Qur’an. The purpose of this study is to provide educators with knowledge on how to practice good Qur’an reading using different methods such as Talaqqi and Tasin methods. This study uses quantitative methods combined with experimental methods. Data collection was carried out by means of a reading test of several Quranic verses used to measure Qur’an reading ability. The research subjects were 35 Santri people. Data analysis used SPSS Statistic 26 application, specifically multiple linear regression analysis. The results of this study show that talaqqi and tahsin methods have a significant influence on students' ability to read the Qur’an. 41.8% of a person's ability to read the Qur’an is influenced by talaqqi and tasin methods, the remaining 58.2% by other factors.